PENGARUH BRAND IMAGE, WORD OF MOUTH, DAN IKLAN TERHADAP MINAT MENABUNG DI BMT SE-KABUPATEN DEMAK - Said, Abu (EQUILIBRIUM, 2016)
The purpose of this article is to empirically examine the influence of brand image, word of mouth, advertising against the interest of saving in BMT Demak. This study uses the approach of field research by questionnaire distributed directly to 312 members of BMT in Demak. The sampling technique used Purposive Sampling. Data were analyzed using regression analysis. The findings indicate that Brand image has an influence on the interest of saving in BMT Demak. This proved that the results t count > t table (2,115> 1,982) with a significance level below 5%. Word of Mouth has an influence on the interest of saving in BMT Demak, this proved that t count > t table (3,270> 1,982) with a significance level below 5%. And advertising has an influence on the interest of saving in BMT Demak, this proved that t count > t table (2,944> 1,982) with a significance level below 5%.